Limited Chances of Speech Improvement After Late Cleft Palate Repair. Issue 4 (June 2015) - Schönmeyr, Björn; Wendby, Lisa; Sharma, Mitali; Raud-Westberg, Liisi; Restrepo, Carolina; Campbell, Alex
<x xml:space="preserve">Abstract</x> Abstract Late primary palatal repair is a common phenomenon, and many patients across the world will be operated on at a far later age than is suggested for normal speech development. Nevertheless, little is known about the speech outcomes after these procedures and conflicting results exist among the few studies performed. In this study, blinded preoperative and postoperative speech recordings from 31 patients operated on at Guwahati Comprehensive Cleft Care Center in Assam, India, older than 7 years were evaluated. Six non-Indian speech and language pathologists evaluated hypernasal resonance and articulation, and 4 local laymen evaluated the speech intelligibility/acceptability of the samples. In 25 of 31 cases, the evaluators could not detect any speech improvement in the postoperative recordings. A clear trend of postoperative improvement was only found in 6 of the 31 patients. Among these 6 patients, lesser clefts were overrepresented. Our findings together with previous studies suggest that late palate repairs have the potential to improve speech, but the probability for improvement and degree of improvement is low, especially in older adolescents and adults with complete clefts.